Pendampingan Belajar Membaca Al-Quran Dengan Benar Bagi Siswa SD dan MI Dusun Labuhan Kecamatan Tambak - Sholihan; Nurul Ayyami Shalehati (CV Putra Publisher, 2024)
Learning to read the Qur'an is an essential duty for Muslims in order to draw closer to Allah SWT and comprehend His teachings. However, in recent years, there has been a decline in interest in learning to read the Qur'an, especially among children. This can be attributed to the lack of parental focus on religious education and the rise of technology, which has made children more engrossed in digital games rather than learning the Qur'an. The objective of this study is to assess the efficacy of a program designed to aid in the proper and accurate recitation of the Qur'an according to the principles of tajweed, as a solution to this issue. The study employed a qualitative approach, utilizing a case study method and action research design. The study participants consisted of elementary school and madrasah students, parents, and mentors (such as teachers or community leaders). Data was collected through observation, in-depth interviews, and documentation, and subsequently analyzed using thematic analysis techniques. The findings of the study demonstrated that the mentoring program significantly enhanced students' ability to read the Qur'an and raised awareness regarding the significance of early religious education. Moreover, this program successfully empowered the local community by engaging them as mentors and teachers, establishing positive collaboration between schools, parents, and the community. In conclusion, this study affirms that structured and continuous mentoring in Qur'an recitation can serve as an effective solution in cultivating a generation that possesses the ability to read, comprehend, and practice Islamic teachings in their daily lives.